WASTE MANAGEMENT STRATEGY BASED ON THE PERSPECTIVE OF SAPTA PESONA (CLEANLINESS) TO INCREASE COMMUNITY INTEREST IN CIMANDE VILLAGE - Maidar Simanihuruk; Sekti Rahardjo (Jurnal Sosial Humaniora, 2021)
The waste management strategy based on the Sapta Pesona (Cleanliness) perspective is one way to provide knowledge to the community that their village where they live is a tourist area that must be clean and free of waste. All tourists will visit the area safe, orderly, clean, cool, beautiful, friendly, and memorable. The research method used is qualitative and quantitative methods. SWOT analysis techniques to improve waste management strategies based on the Santa Persona (Cleanliness) perspective. Data collection method: interviews community leaders, tourist awareness group, and youth organization, questionnaires, observation, and documentation. Qualitative data research: the form of tables and diagrams from the results of the questionnaire and the SWOT analysis. The results of the questionnaire research strongly agree to implement the 3R (reduce-reuse-recycle) program, want to have their own trash cans, and want to throw garbage in their own trash cans carry out environmental cleanliness with mutual cooperation every month. The IFAS analysis was obtained with a value of 1.53, while the EFAS analysis, it was obtained a value of 0.96 then it was brought together in the SWOT analysis quadrant and the results showed that the quadrant 1 area supported aggressive strategies.  This means that the local government of Cimande Tourism Village is carried out a progressive strategy by utilizing the internal strength of Cimande Tourism Village to benefit from external opportunities (opportunities) to support waste management problems so that there are high awareness and interest of the Cimande community about environmental cleanliness to reached Cimande clean. Keywords: Waste Management, Sapta Pesona, Cleanliness, Community Interest, Cimande Village